2001
DOI: 10.1016/s0092-8674(01)00279-3
|View full text |Cite
|
Sign up to set email alerts
|

Histone Acetyltransferase Complexes Stabilize SWI/SNF Binding to Promoter Nucleosomes

Abstract: To investigate the function of SWI/SNF in site-specific chromatin remodeling at promoters, we have used a purified system to analyze its distribution, function, and retention following recruitment by a sequence-specific transcription activator. Activator recruitment of SWI/SNF bound the complex to promoter proximal nucleosomes and led to localized nucleosome disruption. However, retention of SWI/SNF on the promoter required either the continued binding of the transcription activator or acetylated histones. His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
229
2
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(249 citation statements)
references
References 56 publications
(2 reference statements)
15
229
2
3
Order By: Relevance
“…Also shown are anti-GST Western blots of the whole cell lysates used for immunoprecipitation between components of SAGA and SWI/SNF, suggesting a functional relationship between these complexes (Pollard and Peterson, 1997;Roberts and Winston, 1997;Sterner et al, 1999). It has also been shown that acetylation of the N-terminal tails of histones can modify SWI/SNF function and processivity (Logie et al, 1999), and additional genetic and biochemical interactions between SAGA and SWI/ SNF have been reported (Cosma et al, 1999;Hassan et al, 2001;Krebs et al, 2000;Syntichaki et al, 2000). If E1A were acting here simply to ablate SAGA or SWI/SNF function, then the reported synthetic lethality observed in double mutants of SWI/SNF and SAGA would lead to the prediction that expression of E1A in cells containing single mutations that disrupt either complex, would cause death.…”
Section: Discussionmentioning
confidence: 98%
“…Also shown are anti-GST Western blots of the whole cell lysates used for immunoprecipitation between components of SAGA and SWI/SNF, suggesting a functional relationship between these complexes (Pollard and Peterson, 1997;Roberts and Winston, 1997;Sterner et al, 1999). It has also been shown that acetylation of the N-terminal tails of histones can modify SWI/SNF function and processivity (Logie et al, 1999), and additional genetic and biochemical interactions between SAGA and SWI/ SNF have been reported (Cosma et al, 1999;Hassan et al, 2001;Krebs et al, 2000;Syntichaki et al, 2000). If E1A were acting here simply to ablate SAGA or SWI/SNF function, then the reported synthetic lethality observed in double mutants of SWI/SNF and SAGA would lead to the prediction that expression of E1A in cells containing single mutations that disrupt either complex, would cause death.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas Clr3 preferentially targets histone H3 lysine 14, Clr6 displays broad substrate specificity for lysine residues on both histone H3 and H4 tails (50). Deacetylation of histones by these activities may prevent binding of factors such as SWI/SNF that remodel chromatin to provide access to the transcriptional machinery (51). Alternatively, HP1-associated Clr6 and SHREC complexes might act together to remove acetyl groups from histones, and to facilitate the proper positioning of nucleosomes required for higher-order chromatin assembly (22,23,52).…”
Section: Discussionmentioning
confidence: 99%
“…Histone modifications were however found to effect the interaction of SWI/SNF with nucleosomes. Acetylation by SAGA and NuA4 was found to stabilize SWI/ SNF interaction with nucleosome in a bromodomain dependent manner [49,145]. Acetylation of lysine 8 of histone H4 has also been shown to facilitate recruitment of SWI/SNF [146].…”
Section: Role Of Histone Tails and Their Modification In Chromatin Rementioning
confidence: 97%